2020
DOI: 10.3389/fped.2020.586287
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomics Signature of Mild Hypospadias: A Pilot Study

Abstract: Background and Objective: Mild hypospadias is a birth congenital condition characterized by the relocation of the male urethral meatus from its typical anatomical position near the tip of the glans penis, to a lower ventral position up to the brim of the glans corona, which can also be accompanied by foreskin ventral deficiency. For the most part, a limited number of cases have known etiology. We have followed a high-throughput proteomics approach to study the proteome in mild hypospadias patients.Methods: For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…C-Fos is also involved in the downstream JNK pathway signaling to promote cell apoptosis (40). Piñeyro-Ruiz et al also revealed apoptotic signaling pathways during the development of mild hypospadias (16). JNK has been proposed to be associated with mesenchymal cell migration in the process of external male genitalia defect development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C-Fos is also involved in the downstream JNK pathway signaling to promote cell apoptosis (40). Piñeyro-Ruiz et al also revealed apoptotic signaling pathways during the development of mild hypospadias (16). JNK has been proposed to be associated with mesenchymal cell migration in the process of external male genitalia defect development.…”
Section: Discussionmentioning
confidence: 99%
“…Benefiting from innovation in mass spectrometry (MS) and advances in peptide labelling, proteomics study enables the identification and quantification of changes in protein expression in the entire proteome. Recently, Piñeyro-Ruiz et al created a proteomics landscape of mild hypospadias, which highlighted the proteomics characteristics of hypospadias and revealed changes with essential cellular processes related to energy production and apoptosis (16). However, to date, no severe hypospadias proteomics analyses have been introduced.…”
Section: Introductionmentioning
confidence: 99%